Electrochemical Passivation Properties of Valve Transition Metal Carbides - Goehl, Daniel; Ruess, Holger; Mingers, Andrea M.; Mayrhofer, Karl; Schneider, Jochen M.; Ledendecker, Marc (Journal of The Electrochemical Society, 2022)
Transition metal carbides have the potential to be employed as corrosion protective coating for a variety of applications such as e.g. steel based bipolar plates, porous transport layers or as catalyst support in polymer electrolyte membrane fuel cells and water electrolyzers. Yet, little is known of their fundamental, intrinsic corrosion and passivation properties. Herein, we conducted a detailed electrochemical passivation study of various valve transition metal carbides such as titanium carbide, tantalum carbide or tungsten carbide. Via flow cell measurements coupled to an inductively coupled plasma mass spectrometer, the in situ transition metal dissolution was monitored, and the faradaic dissolution efficiency was calculated. Together with the determination of the grown oxide layer via X-ray photoelectron spectroscopy, a thorough evaluation of the passivation efficiency was conducted. Moreover, it was shown that a beneficial stabilization effect can be achieved through alloying of different carbides which paves the way towards tailor-made coatings or catalyst support materials.
CRIS-Team WoS Importer:2022-01-21